加拿大海盆与楚科奇海柱状沉积物中硫酸盐还原菌的分布状况 - 高爱国; 陈皓文; 林学政 (2008)
对取自北极楚科奇海及加拿大海盆的10个沉积物岩芯分别在4℃、25℃培养温度下进行硫酸盐还原菌(SRB)分析,结合首次北极科考海洋沉积物SRB的研究成果,探讨了研究区SRB的分布特点.研究结果表明,4℃与25℃温度培养的SRB含量均为0~2.4×106个.g-1(湿样);4℃时SRB的检出率与平均含量分别为45.5%和2.06×104个.g-1(湿样),25℃培养条件下分别为73.7%和4.70×104个.g-1(湿样);柱状沉积物中SRB的检出率、含量范围、平均含量都明显高于表层沉积物中SRB的相关指标;岩芯中SRB含量分布与采样点的纬度、深度有一定关系,但这种关系不如表层沉积物中SRB分布表现的那么明显;4℃培养时,各层位SRB含量的平均值范围为51~1.2×106个.g-1(湿样),25℃时为2.04×102~2.47×105个.g-1(湿样);在所研究的深度范围内,4℃时培养SRB的垂直变化较为明显,而25℃时SRB的垂直变化相对缓和;根据4℃、25℃2个不同培养温度时SRB的检出率、含量对比看,似乎25℃时更有利于某些SRB的繁衍. Ten sediment core samples(water depth from50 ~3850 m) were collected in the the Canada Basin and the Chukchi Sea during the SecondChinese National Arctic Research Expedition.Each core was sliced on board at 1 cm intervals from 0 ~10 cm and at 2 cm intervals below 10 cm assubsamples,the content of sulfate reducing bacteria(SRB) of these subsamples were analyzed by MPN(Most Probable Number) methed.The contents ofSRB cultivated at both 4℃ and 25℃ ranged from0 to 2.4×106cel.lg-1wet sample and the average SRB cultivated at4℃ and 25℃ were 2.06×104cell.g-1wet sample,and 4.70×104cell.g-1wet sample,respectively.Unlike surface sediments in the study area,the latter shows a tendency to increasefrom low latitude to high latitude,or from shallow water to deep basin.From surface to depths,the content of SRB in sediment changes irregularly,depending on the sedimentary environment.The average contents of SRB cultured at4℃ and 25℃ in the same layer ranged from51 to1.2×106cel.lg-1wet samples and 2.04×102to 2.47×105cel.lg-1wet samples.Comparing the contents,content range,and occurrence rate of SRB cultivated at4℃ and25℃,it seems that 25℃ is more suitable than 4℃for survival and propagation of some SRB. 国家自然科学基金(No.40576060,40376017,40176017)~